FORMULASI ONDE KETAWA BERBAHAN TEPUNG UBI UNGU (Ipomoea batatas L.) DAN TEPUNG MOCAF (Modified Cassava Flour) SEBAGAI SELINGAN TINGGI SERAT: Indonesia - Fadlila, Fithny Aufia; Agus, Sulaeman; Roro Nur, Fauziyah; Mulyo, Gurid Pramintarto Eko (Jurnal Gizi dan Dietetik, 2023)
Onde Ketawa made from purple sweet potato flour and mocaf flour is a high-fiber food product. The purpose of this study was to determine the formulation of purple sweet potato flour and mocaf flour on the quality of onde ketawa as a food interlude that contains high fiber so that it can be given to Diabetes Mellitus patients. The design in this study was experimental with a completely randomized design (RAL). The research method used was hedonic test for liking level and gravimetric enzymatic for food fiber content test. This study involved 30 moderately trained panelists. The data analysis used was Kruskal Wallis then continued with the Mann Whitney test. The hedonic test results showed that formula 2 with a balance of 50% purple sweet potato flour: 50% mocaf flour had the highest level of liking in the aspects of color, taste and overall. The results of the Kruskal Wallis test showed that there were differences in the aspects of taste and overall. The fiber contained in formula 2 is 10.6 grams per 100 grams. Further research needs to be done to determine the IG value of onde ketawa products.